Lower order eigenvalues of the Schrodinger operator - Ma, Bingqing (Communications in Mathematics and Applications, 2014)
Making use of the method introduced by Brands in [4], we consider lower order eigenvalues of the Schrodinger operator in Euclidean domains. We extend an estimate on eigenvalues obtained by Ashbaugh and Benguria in [3].